Shear bond strength to enamel of low-cost adhesive systems an in-vitro study - Rasing, Bon Isid C.; Torno, Joanne Marie A.; Medina III, Vicente O; Medina, Ma. Concepcion (Manila Department of Community Dentistry, University of the Philippines Manila, 2017)
Introduction: Low-cost dental adhesives are popular to many student clinicians and dentists alike because of their price. However, no study has been conducted on these low-cost adhesives. To elucidate on one important factor that could affect clinical performance, this study was conducted to compare the bond strength to enamel low-cost adhesives, with a branded adhesive when used bond to a low-cost composite restorative material and a branded composite material.
Materials and Methods: Sixty bovine teeth were used and the specimens were randomly assigned to six groups (N=10) namely Group 1: Unibond + Natural look Universal Restorative Material, Group 2; Unibond + 3M Filtek Z250xt Dental Composite, Group 3: C-Bond + Natural Look Universal Restorative Material, Group 4: C-Bond + 3M Filtek Z250xt Dental Composite, Group 5: Single Bond Universal + Natural Look Universal Restorative Material, Group 6: Single Bond Universal +3M Filtek Z250xt Dental Composite. The buccal surfaces of the specimens were ground to expose the enamel and mounted in self cure acrylic resin. The surface was etched with 37% phosphoric acid gel (Scotchband Universal etchant) and bonding agents were applied to etched surface. A composite button of 5x3 mm was bonded to the test specimens and subjected to shear load using United Universal Testing Machine at the cross-head speed of 1.0 mm/min. The nature of bond failure was determined using a light microscope at x10 magnification.
Results: Mean shear bond strength in MPa of groups 1,2,,3,4,5, and 6 were 4.9520, 4.9360, 4.7440, 3.4490, 7.3040 and 9.5550 respectively. The mean SBS of the control group (Group 6) is not significantly different from the mean SBS of Group 5 but significantly higher than the mean SBS groups 1,2,3 and 4. Groups 1 and 3 showed 60% adhesive and 40% cohesive, Group 2 showed 90% adhesive and 10% cohesive, Group 4 showed 70% adhesive and 30% cohesive, Groups 5 and 6 showed 50% adhesive and cohesive bond failures
Conclusion: Among the adhesive systems used to bond Filtek Z250XT to enamel. Single Bond produced the highest mean SBS to enamel followed by Unibond and C-Bond. The difference among the groups are significantly different (p<0.5). among the adhesive systems used to bond Natural Look Universal Restorative Material, Single Bond produced the highest mean SBS to enamel followed by Unibond and C-Bond. The difference among the groups are not significantly different (p<0.05).
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila
Keywords: Adhesion; Enamel